About Progeria and Consultation of the Disease (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Purpose of the work: Facing challenges of the progeria which is the cause of the vanishing timing and happiness from the children, leading them to the quick adulthood in a blink of the eyes. Quick description and symptoms of the sickness: Progeria is a specific type of progeroid syndrome, also known as Hutchinson–Gilford syndrome. A single gene mutation is responsible for progeria.